2012
DOI: 10.1186/2046-0481-65-11
|View full text |Cite
|
Sign up to set email alerts
|

Good animal welfare makes economic sense: potential of pig abattoir meat inspection as a welfare surveillance tool

Abstract: During abattoir meat inspection pig carcasses are partially or fully condemned upon detection of disease that poses a risk to public health or welfare conditions that cause animal suffering e.g. fractures. This incurs direct financial losses to producers and processors. Other health and welfare-related conditions may not result in condemnation but can necessitate ‘trimming’ of the carcass e.g. bruising, and result in financial losses to the processor. Since animal health is a component of animal welfare these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 39 publications
2
90
2
1
Order By: Relevance
“…Tail lesion prevalence in the current study was approximately half the prevalence reported in previous studies examining tail lesions in pig herds on the island of Ireland (Harley et al, 2012a;Harley et al, 2014). It is possible that this reflects a decrease in the prevalence of tail lesions in pig herds on the island of Ireland.…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…Tail lesion prevalence in the current study was approximately half the prevalence reported in previous studies examining tail lesions in pig herds on the island of Ireland (Harley et al, 2012a;Harley et al, 2014). It is possible that this reflects a decrease in the prevalence of tail lesions in pig herds on the island of Ireland.…”
Section: Discussioncontrasting
confidence: 43%
“…Tail lesions, particularly more serious lesions, are related to secondary conditions such as abscessation and pleuritic lesions of the lungs (Huey, 1996;Marques et al, 2012), and are associated to a greater extent with trimming of the carcass than milder lesions (Kritas and Morrison, 2007). Nonetheless, even mild tail lesions are associated with carcass condemnations and reduced carcass weights (Harley et al, 2012a and. Therefore, scoring of tail lesions after, rather than before, scalding and dehairing of carcasses offers clear advantages if the information is to be used to inform herd health and welfare management plans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations